Potential of Macrocheles species (Acari: Mesostigmata: Macrochelidae) as control agents of harmful flies (Diptera) and biology of Macrocheles embersoni Azevedo, Castilho and Berto on Stomoxys calcitrans (L.) and Musca domestica L. (Diptera: Muscidae) - Azevedo, Letícia Henrique; Ferreira, Murilo Prudente; Castilho, Raphael de Campos [UNESP]; Cançado, Paulo Henrique Duarte; de Moraes, Gilberto José (Elsevier, 2018)
The stable fly (Stomoxys calcitrans) and horn fly (Haematobia irritans) are mainly parasites of cattle that spend the early phase of their life cycle in decaying vegetation, manure and soil, as members of a wide range of other harmful and beneficial arthropods. Predators of the family Macrochelidae are considered beneficial mites that have been considered promising biological control agents of fly eggs and larvae and of other harmful organisms. The objectives of this study were: a) to compare the predation and oviposition rates of three Macrocheles species, M. embersoni, M. muscaedomesticae and M. robustulus, on six prey species: S. calcitrans, Musca domestica, H. irritans, Bradysia matogrossensis, Rhizoglyphus echinopus and the free living nematode Rhabditella axei; b) to evaluate the life cycle of the best performing predator (M. embersoni) on the most suitable prey species at 30 ± 2 °C, 95 ± 5% RH and in the dark. The three macrochelid species consumed all evaluated prey species, but M. embersoni had higher predation and daily oviposition rates on larvae of S. calcitrans (23.8 larvae consumed and laid about 4.0 eggs, respectively) than other species. Total immature development of M. embersoni was completed in at most about 1.3 days on eggs of S. calcitrans and M. domestica and 1.5 days on R. axei. Macrocheles embersoni produced most eggs (0.28–0.34 female/female/day; rm: 0.28–0.34) on those same prey. The results of this study suggest that M. embersoni is a promising biological control agent of S. calcitrans and M. domestica.
Keywords: Biological control; House fly; Life cycle; Predator; Stable fly